A method for preparing a super-hydrophobic flexible light-to-heat conversion film
Through femtosecond laser direct writing technology, a flexible photothermal conversion film with high efficiency photothermal conversion and superhydrophobic properties was prepared, which solved the problems of high energy consumption and cumbersome process of preparing carbon-based photothermal materials in the prior art, and achieved high performance and low cost photothermal conversion effects.
Patent Information
- Application Number
- CN202510066206.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-16
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-16
AI Technical Summary
The prior art has problems such as high energy consumption, strict reaction conditions, and it is difficult to achieve coordinated regulation of the micromorphology and photothermal properties of the material when preparing carbon-based photothermal materials. The preparation process of flexible photothermal films is cumbersome and costly.
The metal organic frame material is processed into a superhydrophobic flexible photothermal conversion film by using femtosecond laser direct writing technology. The porous carbon-based photothermal material is synthesized through laser photothermal effect, and the surface micro-nano structure is constructed to achieve the efficient photothermal conversion and superhydrophobic properties of the material.
Improves the photothermal conversion performance and superhydrophobic self-cleaning function, reduces the production cost and complexity of processing steps, and extends the service life of wearable thermal therapy equipment.
Smart Images

Figure CN119463264B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar energy photothermal conversion, and in particular to a method for preparing a super-hydrophobic flexible photothermal conversion film. Background Art
[0002] With the development of medical and health care technology, thermal therapy equipment for human health management and disease rehabilitation has received widespread attention. The traditional hospital-centered diagnosis and treatment model has problems such as bulky equipment and tight medical resources. It is urgent to develop flexible wearable heating equipment to meet people's demand for portable thermal therapy. Common heating patches and hot compresses have the advantages of easy use and rapid heating, but at the same time, they have problems such as difficult temperature control and non-reusability. Wearable electric heating products can provide continuous and stable heating, but they need to wear bulky energy supply equipment (such as power banks, etc.) to maintain their operation, which reduces the comfort of wearables. In comparison, converting solar energy in nature into thermal energy is an energy-saving, environmentally friendly and sustainable heating method. In order to efficiently utilize green solar energy and avoid side effects such as heat stroke or skin cancer caused by excessive exposure to ultraviolet rays, it is urgent to develop wearable devices with efficient photothermal conversion performance. By applying them to acupuncture points, joints and other parts of the human body, on-demand and fixed-point thermal therapy can be achieved, providing an effective technical approach to achieve precision medicine.
[0003] Photothermal materials with excellent photothermal conversion capabilities are the basis for achieving efficient conversion of external light energy into thermal energy. Precious metal nanoparticles can absorb photons and convert them into thermal energy through the surface plasmon effect, but they have the problem of high preparation cost and the light absorption efficiency is affected by factors such as particle size and solution concentration. Semiconductor materials such as metal oxides can perform photothermal conversion based on the photothermal electron excitation effect, but they can only absorb light of a specific wavelength, which affects the photothermal conversion performance of sunlight. Carbon-based materials have the ability to absorb sunlight in a wide spectrum range and are one of the most promising photothermal conversion materials. The photothermal conversion ability of carbon-based materials is highly related to their micro-nano structure and specific surface area; carbon-based materials with three-dimensional porous structures can reduce the reflection loss of light and provide a large heat exchange contact area, thereby promoting the photothermal conversion process. Metal-Organic Frameworks (MOFs) are a type of porous crystalline materials with a periodic network structure formed by self-assembly of metal ions and organic ligands through coordination, with the characteristics of adjustable pore structure and high specific surface area. Carbon-based materials derived from high-temperature carbonization of metal-organic frameworks inherit the advantages of large specific surface area and high porosity, and at the same time have high photothermal conversion efficiency, good chemical and thermal stability, and are excellent photothermal materials. The existing technology often uses a high-temperature calcining furnace to decompose and carbonize metal-organic framework raw materials under vacuum or protective atmosphere (such as nitrogen, inert gas, etc.) to prepare carbon-based derivatives, but this method has problems such as high energy consumption, harsh reaction conditions, and difficulty in achieving coordinated regulation of material micromorphology and photothermal performance; in addition, it is necessary to use self-assembly, wet etching, nanoimprinting and other methods to prepare flexible photothermal films and construct micro-nano structures on their surfaces, which has problems such as cumbersome processing steps and high preparation costs. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a super-hydrophobic flexible light-to-heat conversion film to solve the problems existing in the above-mentioned prior art.
[0005] To achieve the above object, the present invention provides the following solutions:
[0006] One of the technical solutions of the present invention: a method for preparing a super-hydrophobic flexible light-to-heat conversion film, comprising the following steps:
[0007] The metal organic framework material is prepared into a flexible film, and then the flexible film is processed by femtosecond laser direct writing to obtain the super hydrophobic flexible photothermal conversion film.
[0008] Furthermore, the metal organic framework material includes ZIF-67 nanoparticles.
[0009] Furthermore, the method for preparing the flexible film comprises the following steps:
[0010] dispersing ZIF-67 nanoparticles in an organic solvent to obtain ZIF-67 ink;
[0011] The ZIF-67 ink is coated on a flexible substrate to obtain the flexible film.
[0012] Further, the particle size of the ZIF-67 nanoparticles is 300-800 nm;
[0013] The concentration of the ZIF-67 ink was 0.05 g / mL.
[0014] Furthermore, the organic solvent is selected from any one of methanol, anhydrous ethanol and N,N-dimethylformamide (DMF).
[0015] Furthermore, the ratio of the amount of the ZIF-67 ink to the area of the flexible substrate is 0.025 mL / cm 2 .
[0016] Furthermore, the flexible substrate is selected from PDMS or Ecoflex.
[0017] Furthermore, the coating method is selected from any one of drop coating, spin coating and spray coating.
[0018] Furthermore, the femtosecond laser direct writing processing is performed twice, the scanning path is flipped 90° twice, and the parameters of the two femtosecond laser direct writings are independent: wavelength of 517 nm, pulse width of 350 fs, repetition rate of 1 MHz, laser power of 50-200 mW, scanning speed of 25-100 mm / s, and direct writing line spacing of 10-50 μm.
[0019] The principle of the present invention is:
[0020] In the process of femtosecond laser direct writing, a femtosecond laser pulse beam is used to act on the metal organic framework flexible film, and the precursor material is carbonized based on the laser photothermal effect to synthesize porous carbon-based photothermal materials. Through a specific combination of laser action parameters, the designable construction of the micro-nano structure on the surface of the film can be achieved simultaneously (it can simultaneously achieve the controllable preparation of high-performance photothermal carbon-based materials and the designable construction of the surface micro-nano structure, that is, the structure of the film surface can be controlled). The micro-nano structure on the surface of the film can reduce the surface reflection of the incident sunlight, thereby improving the photothermal conversion performance, and at the same time make the film surface have super hydrophobic properties.
[0021] The second technical solution of the present invention: a super-hydrophobic flexible photothermal conversion film prepared by the above-mentioned preparation method.
[0022] Technical solution three of the present invention: an application of the above-mentioned super-hydrophobic flexible photothermal conversion film in the preparation of thermal therapy equipment.
[0023] The present invention discloses the following technical effects:
[0024] (1) The super-hydrophobic flexible photothermal conversion film prepared by the present invention has a wide spectrum absorption for incident sunlight. The periodic micro-nano structure on the surface of the film can effectively reduce the macroscopic surface reflection and thus improve the photothermal conversion performance. In addition, the periodic micro-nano structure on the surface of the film can also make the film have excellent super-hydrophobic self-cleaning function, which can reduce the influence of pollution sources such as surface sweat on the thermal therapy device attached to the skin surface, and effectively extend the service life of the wearable thermal therapy device.
[0025] (2) The present invention utilizes femtosecond laser direct writing technology to synthesize carbon-based photothermal materials based on the laser photothermal effect to induce carbonization of the metal organic framework in the processing area, and realizes the micro-nano structuring of the film surface, which has the advantages of high processing accuracy, small heat-affected area, simple processing technology, and flexible and designable structure; the femtosecond laser pulse beam is used to act on the metal organic framework flexible film, which can not only synthesize derivative carbon-based materials with high-efficiency photothermal performance, but also construct surface micro-nano structures, improve the photothermal conversion performance by reducing surface reflection, and make the surface have super-hydrophobic self-cleaning properties, reduce the influence of environmental pollutants on the photothermal conversion film, and extend its service life. The preparation method of the present invention solves the problems that the existing processing technology needs to use multiple steps to synthesize photothermal materials, regulate the photothermal conversion performance of photothermal materials, and construct surface micro-nano structures, resulting in cumbersome processing steps and high preparation costs.
[0026] (3) The preparation method of the present invention can achieve the regulation of the micro-nano structure on the surface of the film by adjusting the laser parameter combination of femtosecond laser direct writing, thereby improving the photothermal conversion performance and self-cleaning performance of the film. In addition, the preparation method of the present invention has the characteristics of simple process flow, low preparation cost, and designable processing. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0028] Figure 1 Schematic diagram of the preparation process of super-hydrophobic flexible light-to-heat conversion film;
[0029] Figure 2 The optical photograph and scanning electron microscope image of the ZIF-67 nanoparticles prepared in Example 1 and the absorption spectrum of the photothermal conversion film prepared in Example 1 are shown in Figures 1 and 2, wherein a) is an optical photograph, b) is a scanning electron microscope image, and c) is an ultraviolet-visible-near infrared absorption spectrum of the photothermal conversion film prepared in Example 1;
[0030] Figure 3 The scanning electron microscope images of the light-to-heat conversion films prepared in the examples and comparative examples, wherein a) is Example 1, b) is Example 2, c) is Comparative Example 1, d) is Comparative Example 2, e) is Comparative Example 3, f) is Comparative Example 4, g) is a partial enlarged view of Comparative Example 3, and h) is a partial enlarged view of Comparative Example 4;
[0031] Figure 4 The photothermal conversion performance test diagrams of the photothermal conversion films prepared in the embodiments and comparative examples under the illumination intensity of 1 sun, wherein a) is the temperature-time curve of the photothermal conversion films prepared in embodiments 1 to 4, b) is the infrared thermal image of the photothermal conversion film prepared in embodiment 1 at a steady state, c) is the infrared thermal image of the photothermal conversion film prepared in embodiment 2 at a steady state, d) is the infrared thermal image of the photothermal conversion film prepared in embodiment 3 at a steady state, e) is the infrared thermal image of the photothermal conversion film prepared in embodiment 4 at a steady state, f) is the infrared thermal image of the photothermal conversion film prepared in comparative example 1 at a steady state, g) is the infrared thermal image of the thermal conversion film prepared in comparative example 2 at a steady state, h) is the infrared thermal image of the photothermal conversion film prepared in comparative example 3 at a steady state, and i) is the infrared thermal image of the photothermal conversion film prepared in comparative example 4 at a steady state;
[0032] Figure 5 The temperature-time curves of the photothermal conversion films prepared under different laser parameter combinations under 1 sun illumination intensity, wherein a) is the temperature-time curve of the photothermal conversion films prepared in Example 1 and Comparative Examples 1-2, and b) is the temperature-time curve of the photothermal conversion films prepared in Example 1-2 and Comparative Examples 3-4;
[0033] Figure 6 The stretchability test diagrams of the light-to-heat conversion films prepared using different substrates, wherein a) is the stretchability of Example 1 (PDMS flexible substrate), b) is the stretchability of Example 3 (Ecoflex flexible substrate), and c) is the effect of different stretching degrees on the steady-state temperature of the two light-to-heat conversion films;
[0034] Figure 7 The surface superhydrophobicity test diagram of the light-to-heat conversion film prepared in Example 1 under room temperature and high humidity environment, wherein a) is the change of contact angle and rolling angle within 30 days, b) is the change of contact angle within 30 days, and c) is the change of rolling angle within 30 days;
[0035] Figure 8The surface superhydrophobicity test diagram of the light-to-heat conversion films prepared in Examples 1 to 4 and Comparative Examples 1 to 4, wherein a) is the contact angle and the rolling angle of the light-to-heat conversion films prepared in Examples 1 to 4, b) is the contact angle and the rolling angle of the light-to-heat conversion films prepared in Comparative Examples 1 to 4, and c) is the change in steady-state temperature of the light-to-heat conversion films prepared in Example 1 and Comparative Examples 1 to 4 under room temperature and high humidity environments within 30 days;
[0036] Fig. 9 The photothermal conversion performance test graph and surface superhydrophobicity test graph of the photothermal conversion film prepared in Comparative Example 5 under 1 sun illumination intensity, wherein a) is the temperature-time curve and the infrared thermal image at steady state of the photothermal conversion film prepared in Comparative Example 5, b) is the contact angle and the rolling angle of the photothermal conversion film prepared in Comparative Example 5, and c) is the change of steady-state temperature of the photothermal conversion film prepared in Comparative Example 5 under room temperature and high humidity environment within 30 days. DETAILED DESCRIPTION
[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0042] In a first aspect, the present invention provides a method for preparing a super-hydrophobic flexible light-to-heat conversion film, comprising the following steps:
[0043] (1) Dissolve 3.64 g of Co(NO3)2·6H2O in 20 mL of methanol to obtain a Co(NO3)2 solution; dissolve 4.11 g of 2-methylimidazole (2-MIM) in 20 mL of methanol to obtain a 2-MIM solution;
[0044] The 2-MIM solution was added to the Co(NO3)2 solution, and after magnetic stirring at 600 rpm for 15 min, the solution was allowed to stand for 30 min and allowed to settle naturally to obtain ZIF-67 nanoparticles with a particle size of 300-800 nm.
[0045] (2) dispersing ZIF-67 nanoparticles in an organic solvent to obtain a ZIF-67 ink with a concentration of 0.05 g / mL;
[0046] In a specific embodiment of the present invention, the organic solvent is selected from any one of methanol, anhydrous ethanol and N,N-dimethylformamide (DMF).
[0047] (3) uniformly coating the ZIF-67 ink on a clean flexible substrate to obtain a ZIF-67 flexible film;
[0048] In a specific embodiment of the present invention, the ratio of the amount of ZIF-67 ink to the area of the flexible substrate is 0.025 mL / cm 2 .
[0049] In a specific embodiment of the present invention, the flexible substrate is selected from PDMS or Ecoflex.
[0050] In a specific embodiment of the present invention, the coating method is selected from any one of drop coating, spin coating and spray coating.
[0051] (4) The ZIF-67 flexible film was processed by femtosecond laser direct writing technology. Based on the laser photothermal effect, carbon-based photothermal materials were induced and surface micro-nano structures were constructed to obtain a super-hydrophobic flexible photothermal conversion film.
[0052] The schematic diagram of the preparation process of super-hydrophobic flexible light-to-heat conversion film is shown in Figure 1 .
[0053] In a specific embodiment of the present invention, the number of femtosecond laser direct writing processing is 2 times, the scanning path is flipped 90° twice, and the parameters of the two femtosecond laser direct writing are independent: wavelength is 517 nm, pulse width is 350 fs, repetition rate is 1 MHz, laser power is 50~200 mW, scanning speed is 25~100 mm / s, and direct writing line spacing is 10~50 μm.
[0054] By regulating the laser power, laser direct writing speed and laser direct writing line spacing, the photothermal conversion properties and surface micro-nano structure of the processed product can be in situ controlled to achieve the preparation of flexible photothermal conversion films with surface super-hydrophobic properties.
[0055] In a second aspect of the present invention, a super-hydrophobic flexible light-to-heat conversion film prepared by the above-mentioned preparation method is provided.
[0056] A third aspect of the present invention provides an application of the above-mentioned super-hydrophobic flexible light-to-heat conversion film in the preparation of thermal therapy equipment.
[0057] Unless otherwise specified, the room temperature in the present invention is 25±2°C, the humidity is high humidity (75±5%), and the illumination intensity of one sun is 1 kW / m 2 .
[0058] In the embodiments of the present invention, the parts not described in detail are conventional operating methods in the art and are not the focus of the present invention, so they are not described in detail here. For example, the specific process of washing the precipitate after the reaction with an organic solvent is a common method in the art.
[0059] All raw materials used in the examples of the present invention were purchased from commercial sources. Among them, Co(NO3)2·6H2O and 2-MIM were purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; PDMS was purchased from Dow Corning, Ecoflex was purchased from Smooth-On; methanol, anhydrous ethanol and N,N-dimethylformamide (DMF) amide were purchased from Guangzhou Chemical Reagent Factory.
[0060] Example 1
[0061] A method for preparing a super-hydrophobic flexible light-to-heat conversion film:
[0062] (1) Synthesis of ZIF-67 nanoparticles:
[0063] 3.64 g of Co(NO3)2·6H2O was added to 20 mL of methanol and magnetically stirred at 600 rpm for 15 min to obtain a Co(NO3)2 solution; 4.11 g of 2-MIM was added to 20 mL of methanol and magnetically stirred at 600 rpm for 15 min to obtain a 2-MIM solution;
[0064] The 2-MIM solution was added to the Co(NO3)2 solution, and after magnetic stirring at 600 rpm for 15 min, the solution was allowed to stand for 30 min to settle naturally, and then centrifuged and washed three times (the centrifugal speed was 5000 rpm, the centrifugal time was 5 min, and the solvent used for washing was prepared by mixing methanol and anhydrous ethanol in a volume ratio of 1:1) until the supernatant was transparent. The lower precipitate was then removed and vacuum dried (drying temperature was 70 °C, drying time was 3 h) to obtain ZIF-67 nanoparticles (particle size was 300~800 nm). The optical photograph and scanning electron microscope image of the ZIF-67 nanoparticles are shown in Figure 2 , Figure 2 In the figure, a) is an optical photograph, and b) is a scanning electron microscope image.
[0065] (2) Preparation of ZIF-67 ink: 0.5 g of ZIF-67 nanoparticles were added to 10 mL of DMF and magnetically stirred at 400 rpm for 4 h to obtain a uniformly dispersed ZIF-67 ink with a concentration of 0.05 g / mL.
[0066] (3) Preparation of ZIF-67 flexible film: PDMS prepolymer (component A) and curing agent (component B) were mixed in a mass ratio of 10:1 and cured at 80 °C for 1 h to obtain a PDMS flexible substrate. The substrate surface was cleaned with anhydrous ethanol, and then 0.5 mL of ZIF-67 ink with a concentration of 0.05 g / mL was evenly dropped on a 20 cm 2 The ZIF-67 flexible film was obtained after being naturally dried for 1 h on a PDMS flexible substrate.
[0067] (4) Synthesis and structuring of metal-organic framework-derived carbon materials based on laser photothermal effect: The laser beam was focused on the ZIF-67 flexible film plane through a field mirror, and the metal-organic framework film was processed by controlling the laser scanning path through a program. The laser parameters used during processing were: wavelength of 517 nm, pulse width of 350 fs, repetition rate of 1 MHz, and two femtosecond laser direct writing operations. The laser power of the first femtosecond laser direct writing was 100 mW, the scanning speed was 25 mm / s, and the line spacing was 50 μm. The scanning path was flipped 90° for the second femtosecond laser direct writing. The laser power of the second femtosecond laser direct writing was 50 mW, the scanning speed was 50 mm / s, and the line spacing was 25 μm. A superhydrophobic flexible photothermal conversion film was obtained.
[0068] Example 2
[0069] The same as Example 1, except that the laser power of the first femtosecond laser direct writing is 200 mW, the scanning speed is 100 mm / s, the line spacing is 50 μm, and the scanning path is flipped 90° for the second femtosecond laser direct writing. The laser power of the second femtosecond laser direct writing is 50 mW, the scanning speed is 25 mm / s, and the line spacing is 10 μm.
[0070] Example 3
[0071] The same as Example 1, except that the substrate is an Ecoflex flexible substrate. The specific steps for preparing the Ecoflex flexible substrate are: mixing component A and component B of Ecoflex in a mass ratio of 1:1, curing at 60° C. for 15 min to obtain the Ecoflex flexible substrate, and cleaning the substrate surface with anhydrous ethanol.
[0072] Example 4
[0073] The same as Example 1, except that DMF in step (2) is replaced by anhydrous ethanol.
[0074] Comparative Example 1
[0075] The same as Example 1, except that the laser power of the first femtosecond laser direct writing is 100 mW, the scanning speed is 25 mm / s, the line spacing is 25 μm, and the scanning path is flipped 90° for the second femtosecond laser direct writing. The laser power of the second femtosecond laser direct writing is 25 mW, the scanning speed is 10 mm / s, and the line spacing is 25 μm.
[0076] Comparative Example 2
[0077] The same as Example 1, except that the laser power of the first femtosecond laser direct writing is 200 mW, the scanning speed is 200 mm / s, the line spacing is 50 μm, and the scanning path does not need to be flipped for the second femtosecond laser direct writing. The laser power of the second femtosecond laser direct writing is 25 mW, the scanning speed is 50 mm / s, and the line spacing is 25 μm.
[0078] Comparative Example 3
[0079] The same as Example 1, except that the laser power of the first femtosecond laser direct writing is 25 mW, the scanning speed is 100 mm / s, the line spacing is 25 μm, and the scanning path is flipped 90° for the second femtosecond laser direct writing. The laser power of the second femtosecond laser direct writing is 25 mW, the scanning speed is 100 mm / s, and the line spacing is 25 μm.
[0080] Comparative Example 4
[0081] The same as Example 1, except that the laser power of the first femtosecond laser direct writing is 300 mW, the scanning speed is 100 mm / s, the line spacing is 25 μm, and the scanning path is flipped 90° for the second femtosecond laser direct writing. The laser power of the second femtosecond laser direct writing is 300 mW, the scanning speed is 100 mm / s, and the line spacing is 25 μm.
[0082] Effect Example 1
[0083] (1) The UV-visible-near infrared absorption spectrum of the light-to-heat conversion film prepared in Example 1 is shown in Figure 2 As shown in Figure c, the material prepared by the present invention can absorb light of different wavelengths, and the light absorption rate is greater than 95% in the wavelength range of 250~2500 nm.
[0084] (2) The scanning electron microscope images of the light-to-heat conversion films prepared in Examples 1-2 and Comparative Examples 1-4 are shown in Figure 3 ; Figure 3 In the figure, a) is Example 1, b) is Example 2, c) is Comparative Example 1, d) is Comparative Example 2, e) is Comparative Example 3, f) is Comparative Example 4, g) is a partial enlarged view of Comparative Example 3, and h) is a partial enlarged view of Comparative Example 4.
[0085] from Figure 3 It can be seen from the figures a) to d) that the light-to-heat conversion films prepared in Examples 1 to 2 and Comparative Examples 1 to 2 both have periodic micro-nano structures that can reduce macroscopic surface reflections, and the density of the periodic micro-nano structures on the surfaces of Examples 1 to 2 is greater than that of Comparative Examples 1 to 2, so the reduction of macroscopic surface reflections is more significant and effective; in addition, the density of the periodic micro-nano structures on the surface also affects the strength of the (super) hydrophobicity of the film, thereby affecting the film's ability to resist environmental interference.
[0086] from Figure 3 It can be seen from Figures e) to f) that the light-to-heat conversion films prepared in Comparative Examples 3 and 4 do not have a periodic micro-nano structure that can reduce macroscopic surface reflection, and the reaction degree of Comparative Example 3 is low and no micro-nano structure is formed, while the micro-nano structure of Comparative Example 4 is over-reacted and destroyed; in addition, whether the surface has a periodic micro-nano structure affects whether the film has (super) hydrophobicity, which in turn affects the film's ability to resist environmental interference.
[0087] (3) The photothermal conversion performance test diagram of the photothermal conversion films prepared in the examples and comparative examples under 1 sun illumination intensity is shown in Figure 4, wherein a) is the temperature-time curve of the light-heat conversion film prepared in Examples 1 to 4, b) is the infrared thermal image of the light-heat conversion film prepared in Example 1 at a steady state, c) is the infrared thermal image of the light-heat conversion film prepared in Example 2 at a steady state, d) is the infrared thermal image of the light-heat conversion film prepared in Example 3 at a steady state, e) is the infrared thermal image of the light-heat conversion film prepared in Example 4 at a steady state, f) is the infrared thermal image of the light-heat conversion film prepared in Comparative Example 1 at a steady state, g) is the infrared thermal image of the light-heat conversion film prepared in Comparative Example 2 at a steady state, h) is the infrared thermal image of the light-heat conversion film prepared in Comparative Example 3 at a steady state, and i) is the infrared thermal image of the light-heat conversion film prepared in Comparative Example 4 at a steady state.
[0088] The temperature-time curves of the photothermal conversion films prepared under different laser parameter combinations under 1 sun illumination intensity are shown in Figure 5 , wherein a) is the temperature-time curve of the light-to-heat conversion film prepared in Example 1 and Comparative Examples 1-2, and b) is the temperature-time curve of the light-to-heat conversion film prepared in Example 1-2 and Comparative Examples 3-4.
[0089] from Figure 4 It can be seen from Figures a) and b) that the surface temperature of the light-to-heat conversion film prepared in Example 1 can be rapidly increased to a steady-state temperature of 51.2° C. under an illumination intensity of 1 sun.
[0090] from Figure 4 It can be seen from Figures a) and c) that the surface temperature of the light-to-heat conversion film prepared in Example 2 can be rapidly increased to a steady-state temperature of 50.8°C under an illumination intensity of 1 sun.
[0091] from Figure 4 It can be seen from Figures a) and d) that the surface temperature of the light-to-heat conversion film prepared in Example 3 can be rapidly increased to a steady-state temperature of 52.5°C under an illumination intensity of 1 sun.
[0092] from Figure 4 It can be seen from Figure a) and Figure e) that the surface temperature of the light-to-heat conversion film prepared in Example 4 can be rapidly increased to a steady-state temperature of 51.0°C under an illumination intensity of 1 sun.
[0093] from Figure 4 f) Figure and Figure 5 As can be seen from Figure a), the surface temperature of the light-to-heat conversion film prepared in Comparative Example 1 can reach a steady-state temperature of 49.8°C under an illumination intensity of 1 sun.
[0094] from Figure 4 g) Figure and Figure 5As can be seen from Figure a), the surface temperature of the light-to-heat conversion film prepared in Comparative Example 2 can reach a steady-state temperature of 48.9°C under an illumination intensity of 1 sun.
[0095] from Figure 4 h) Figure and Figure 5 As can be seen from Figure b), the surface temperature of the light-to-heat conversion film prepared in Comparative Example 3 only reaches a steady-state temperature of 45.1°C under an illumination intensity of 1 sun.
[0096] from Figure 4 i) Figure and Figure 5 As can be seen from Figure b), the surface temperature of the light-to-heat conversion film prepared in Comparative Example 4 only reaches a steady-state temperature of 44.2°C under an illumination intensity of 1 sun.
[0097] (4) The tensile test diagram of the photothermal conversion film prepared using different substrates is shown in Figure 6 , wherein a) is the stretchability of Example 1 (PDMS flexible substrate), b) is the stretchability of Example 3 (Ecoflex flexible substrate), and c) is the effect of different stretching degrees on the steady-state temperature of the two light-to-heat conversion films.
[0098] from Figure 6 As can be seen from the figure a), the light-to-heat conversion film prepared in Example 1 can be stretched from the initial 0% to 150% and still maintain excellent light-to-heat conversion performance. Further increasing the stretching deformation will cause the film to break; Figure 6 As can be seen from the figure c), the photothermal performance of the photothermal conversion film prepared in Example 1 does not decrease significantly during the process of stretching from the initial 0% to 100%, and the excellent photothermal conversion performance can be maintained even in the stretched state.
[0099] from Figure 6 As can be seen from the figure b), the light-to-heat conversion film prepared in Example 3 can be stretched from the initial 0% to 250% and still maintain excellent light-to-heat conversion performance. Further increasing the stretching deformation will cause the film to break; Figure 6 As can be seen from the figure c), the photothermal performance of the photothermal conversion film prepared in Example 3 does not decrease significantly during the process of stretching from the initial 0% to 200%, and the excellent photothermal conversion performance can be maintained in the stretched state.
[0100] The slight difference in light-to-heat conversion between Example 3 and Example 1 is due to the fact that the thermal conductivity of the Ecoflex flexible substrate is poorer than that of the PDMS flexible substrate, which slightly increases the steady-state temperature. The difference in stretchability between Example 3 and Example 1 is due to the fact that the Ecoflex flexible substrate has a lower modulus and greater toughness, and can withstand greater tensile deformation. There is no significant difference in the other properties, indicating that the method for processing and preparing light-to-heat conversion films based on metal organic framework-derived carbon materials is universal for similar flexible substrates.
[0101] (5) The surface super-hydrophobicity test diagram of the light-to-heat conversion film prepared in Example 1 is shown in Figure 7 , where a) is the change in contact angle and rolling angle of the photothermal conversion film at room temperature and high humidity environment within 30 days, b) is the change in contact angle of the photothermal conversion film at room temperature and high humidity environment within 30 days, and c) is the change in rolling angle of the photothermal conversion film at room temperature and high humidity environment within 30 days.
[0102] The surface super-hydrophobicity test graph of the light-to-heat conversion films prepared in Examples 1 to 4 and Comparative Examples 1 to 4 is shown in Figure 8 , wherein a) is the contact angle and the rolling angle of the light-to-heat conversion film prepared in Examples 1 to 4, b) is the contact angle and the rolling angle of the light-to-heat conversion film prepared in Comparative Examples 1 to 4, and c) is the change in steady-state temperature of the light-to-heat conversion film prepared in Examples and Comparative Examples 1 to 4 under room temperature and high humidity environments within 30 days.
[0103] from Figure 7 It can be seen from Figures a), b) and c) that the contact angle of the light-to-heat conversion film prepared in Example 1 is 155.5°, the rolling angle is 4.2°, and the contact angle remains greater than 150° and the rolling angle remains less than 10° within 30 days. At the same time, the samples prepared using the same processing parameters have good consistency.
[0104] from Figure 8 As can be seen from the figure c), the surface super-hydrophobicity can reduce the influence of pollutants in the environment on the photothermal film and maintain durable and efficient photothermal conversion characteristics. It can be seen that the photothermal conversion film prepared by the preparation method of the embodiment of the present invention has efficient photothermal conversion performance, excellent surface super-hydrophobicity, good stretchability and long service life.
[0105] from Figure 8 As can be seen from the figure a), the contact angle of the photothermal conversion film prepared in Example 2 is 156.4°, and the rolling angle is 3.2°; the contact angle of the photothermal conversion film prepared in Example 3 is 155.8°, and the rolling angle is 4.1°; the contact angle of the photothermal conversion film prepared in Example 4 is 155.4°, and the rolling angle is 4.2°, which also has excellent surface superhydrophobicity. In addition, there is no significant difference in performance between Example 4 and Example 1, indicating that the ZIF-67 ink dispersed in different organic solvents has no significant effect on the performance of the prepared photothermal conversion film.
[0106] from Figure 8 As can be seen from the figure b), the contact angle of the light-to-heat conversion film prepared in Comparative Example 1 is 124.2°, and the rolling angle is 13.3°, which does not meet the super-hydrophobic condition, indicating that it is only hydrophobic but not super-hydrophobic; Figure 8As can be seen from Figure c), its photothermal performance decreased significantly within 30 days, indicating that the non-superhydrophobic photothermal conversion film is greatly affected by pollutants in the environment.
[0107] from Figure 8 As can be seen from the figure b), the contact angle of the light-to-heat conversion film prepared in Comparative Example 2 is 87.5°, and the rolling angle is 23.2°, which does not meet the hydrophobic condition, indicating that it is not hydrophobic; Figure 8 As can be seen from Figure c), its photothermal performance decreases more significantly within 30 days, indicating that the non-hydrophobic photothermal conversion film is more affected by pollutants in the environment.
[0108] The test found that there are differences in the photothermal conversion performance and stability of the photothermal conversion films prepared in Comparative Examples 1 and 2 and Example 1. The density of the surface structure of the photothermal conversion film in Example 1 is larger, which can significantly reduce the reflection of light and extend the light path, promote light absorption, and enhance thermal radiation performance. Therefore, the performance and stability of the photothermal conversion film are better than those of Comparative Examples 1 and 2; in addition, Comparative Example 1 is only hydrophobic but not super-hydrophobic, and Comparative Example 2 is not hydrophobic, which means that the micro-nano structures of Comparative Examples 1 and 2 do not have super-hydrophobic properties and are therefore greatly affected by the environment; from the perspective of the decline in photothermal performance within 30 days, the decline in Example 1 is significantly smaller than that in Comparative Example 1, and the decline in Comparative Example 1 is smaller than that in Comparative Example 2, which also illustrates the importance of super-hydrophobicity to the stability of the photothermal conversion film.
[0109] from Figure 8 As can be seen from the figure b), the contact angle of the light-to-heat conversion film prepared in Comparative Example 3 is 82.2°, and the rolling angle is 28.4°, which does not meet the hydrophobic condition, indicating that it does not have (super) hydrophobicity; Figure 8 As can be seen from the figure c), its photothermal performance decreases more significantly within 30 days, indicating that the worse the hydrophobicity of the photothermal conversion film is, the greater the impact of pollutants in the environment. The reason for the above-mentioned problems of the photothermal conversion film prepared in Comparative Example 3 is that the energy density under the parameter combination adopted by the femtosecond laser direct writing in Comparative Example 3 is low, which makes the carbonization degree of the metal organic framework low, and cannot form a micro-nano structure that can promote light absorption. Therefore, compared with Examples 1 and 2 and Comparative Examples 1 and 2, which form the synergistic effect of photothermal materials and micro-nano structures, the photothermal performance of the photothermal conversion film in Comparative Example 3 is significantly reduced. In addition, since the surface is not hydrophobic (and the hydrophobicity is worse), the photothermal performance of the photothermal conversion film decreases more significantly within 30 days and is more affected by the environment.
[0110] from Figure 8 As can be seen from the figure b), the contact angle of the light-to-heat conversion film prepared in Comparative Example 4 is 146.4°, and the rolling angle is 8.3°, which does not meet the super-hydrophobic condition, indicating that it is only hydrophobic but not super-hydrophobic; Figure 8As can be seen from the figure c), except for Example 1, its photothermal performance has the least obvious decline within 30 days, indicating that the better the hydrophobicity of the photothermal conversion film, the less it is affected by pollutants in the environment. The reason for the above problems of the photothermal conversion film prepared in Comparative Example 4 is that the energy density under the parameter combination adopted by the femtosecond laser direct writing in Comparative Example 4 is too large, and the laser photothermal effect significantly causes the processed material to ablate, destroying the integrity of the film structure and reducing its photothermal conversion performance. In addition, due to the hydrophobicity close to super hydrophobicity, its photothermal performance has the smallest decline within 30 days compared with Comparative Examples 1, 2, and 3, and is less affected by the environment.
[0111] Comparative Example 5
[0112] The same as Example 1, except that bacterial cellulose is mixed into the ZIF-67 ink to prepare a mixed ink, and then a flexible self-supporting metal organic framework film is prepared by vacuum filtration. The specific steps are as follows:
[0113] Preparation of ZIF-67-cellulose mixed ink: 0.5 g of ZIF-67 nanoparticles and 0.05 g of bacterial cellulose were added to 10 mL of DMF and magnetically stirred at 400 rpm for 4 h to obtain a mixed ink with a uniformly dispersed ZIF-67 and cellulose mass ratio of 10:1.
[0114] Preparation of ZIF-67 flexible self-supporting film: 0.25 mL of ZIF-67 mixed ink was vacuum filtered to obtain a film with an area of 10 cm 2 The ZIF-67 flexible self-supporting film (the amount of ZIF-67 mixed ink and the area ratio of the film were kept at 0.025 mL / cm 2 ).
[0115] Fig. 9 The photothermal conversion performance test graph and surface superhydrophobicity test graph of the photothermal conversion film prepared in Comparative Example 5 under 1 sun illumination intensity, wherein a) is the temperature-time curve and the infrared thermal image at steady state of the photothermal conversion film prepared in Comparative Example 5, b) is the contact angle and the rolling angle of the photothermal conversion film prepared in Comparative Example 5, and c) is the change of steady-state temperature of the photothermal conversion film prepared in Comparative Example 5 under room temperature and high humidity environment within 30 days.
[0116] from Fig. 9 As can be seen from Figure a), the surface temperature of the light-to-heat conversion film prepared in Comparative Example 5 can reach a steady-state temperature of 50.9°C under an illumination intensity of 1 sun.
[0117] from Fig. 9 As can be seen from the figure b), the contact angle of the light-to-heat conversion film prepared in Comparative Example 5 is 65.4°, and the rolling angle is 35.9°, which does not meet the hydrophobic condition, indicating that it is not hydrophobic.
[0118] from Fig. 9 As can be seen from Figure c), its photothermal performance decreased significantly within 30 days, indicating that the vacuum-filtered photothermal conversion membrane using ZIF-67 mixed cellulose has good hydrophilicity and is greatly affected by pollutants in the environment.
[0119] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing a super-hydrophobic flexible light-to-heat conversion film, characterized in that: The following steps are involved: The metal organic framework material is prepared into a flexible film, and then the flexible film is processed by femtosecond laser direct writing to obtain the super hydrophobic flexible photothermal conversion film; The metal organic framework material includes ZIF-67 nanoparticles; The method for preparing the flexible film comprises the following steps: dispersing ZIF-67 nanoparticles in an organic solvent to obtain ZIF-67 ink; Applying the ZIF-67 ink on a flexible substrate to obtain the flexible film; The flexible substrate is selected from PDMS or Ecoflex; The femtosecond laser direct writing process was performed twice, and the scanning path was flipped 90° twice. The parameters of the two femtosecond laser direct writing processes were independent: wavelength of 517 nm, pulse width of 350 fs, repetition rate of 1 MHz, laser power of 50-200 mW, scanning speed of 25-100 mm / s, and direct writing line spacing of 10-50 μm.
2. The preparation method according to claim 1, characterized in that: The particle size of the ZIF-67 nanoparticles is 300-800 nm; And / or, the concentration of the ZIF-67 ink is 0.05 g / mL.
3. The preparation method according to claim 1, characterized in that: The ratio of the amount of the ZIF-67 ink to the area of the flexible substrate is 0.025 mL / cm 2 .
4. A super-hydrophobic flexible light-to-heat conversion film prepared by the preparation method according to any one of claims 1 to 3.
5. Use of the super-hydrophobic flexible photothermal conversion film according to claim 4 in the preparation of thermal therapy equipment.
Citation Information
Patent Citations
Maskless femtosecond laser manufacturing method for super-hydrophobic and anti-reflective surface
CN107243697A
Photothermal conversion film based on laser-induced metal organic framework derivative and preparation method and system thereof
CN118602604A